India’s XIIth Plan (2011/’12 – 2016/’17) on Capacity Addition - 88,500 Megawatt - Pun, S B (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Not Available.HYDRO Nepal JournalJournal of Water, Energy and EnvironmentIssue: 17, July 2015